2007
DOI: 10.1016/j.ijrobp.2007.07.2369
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Radiotherapy Planning on Decreasing Gross Tumor Volumes as Seen on Megavoltage Computed Tomography Images

Abstract: Purpose: To evaluate gross tumor volume (GTV) changes for patients with non-small-cell lung cancer by using daily megavoltage (MV) computed tomography (CT) studies acquired before each treatment fraction on helical tomotherapy and to relate the potential benefit of adaptive image-guided radiotherapy to changes in GTV. Methods and Materials: Seventeen patients were prescribed 30 fractions of radiotherapy on helical tomotherapy for non-small-cell lung cancer at London Regional Cancer Program from Dec 2005 to Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
159
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(169 citation statements)
references
References 26 publications
6
159
2
2
Order By: Relevance
“…However, Siker et al (2006) found no apparent correlations between tumor regression and chemotherapy, pathology, and the original tumor volume. The tumor regression rate had no important correlations with the original tumor volume, radiotherapy duration, pathological type and stage, and tumor density; specifically, the change in primary lesion tumor volume did not correlate with either patient-related properties or tumor-intrinsic characteristics (Woodford et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, Siker et al (2006) found no apparent correlations between tumor regression and chemotherapy, pathology, and the original tumor volume. The tumor regression rate had no important correlations with the original tumor volume, radiotherapy duration, pathological type and stage, and tumor density; specifically, the change in primary lesion tumor volume did not correlate with either patient-related properties or tumor-intrinsic characteristics (Woodford et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, the tumor volume shows no apparent change upon repeated localizations, it is not feasible to effectively reduce the dose volume parameter of the normal lung tissues. Therefore, there is no significant association with an increased irradiation dose (Woodford et al, 2007). The key to effectively reducing the dose volume parameter is to modify the treatment plan in a timely manner as the tumor volume shows an apparent change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shrinkage of the gross tumor volume (GTV) indicates that irradiation field shapes and field sizes could or should be adapted during the treatment course, thus NSCLC patients are re-imaged and re-planned during the treatment is a possible strategy to improve treatment delivery. It is reported that if GTV decreases by greater than 30% at any point in the first 20 fractions of treatment, i.e., 40Gy, it may be appropriate to adapt the plan to improve sparing of normal tissues, adaptive planning is appropriate to further improve the therapeutic ratio (Woodford et al, 2007). On the other hand, acurate delineation of the primary tumor and involved lymph nodes is a key requisite for precise radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor shrinkage is often observed during radiation therapy of NSCLC (1)(2)(3)(4)(5)(6). The most commonly proposed planning paradigm to handle tumor shrinkage is adaptive radiation therapy (ART) (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%